IMPLEMENTASI DETEKSI GANGGUAN PERTUMBUHAN-PERKEMBANGAN BALITA (USIA 1-5 TAHUN) DENGAN STIMULASI, DETEKSI DAN INTERVENSI DINI TUMBUH KEMBANG (SDIDTK) DI POSYANDU KUCAI KELURAHAN TELUK KABUPATEN BANYUMAS - Septerina Purwandani; Amelia Puspita Wijaya (Universitas Harapan Bangsa Purwokerto, 2009)
Early detection through SDIDTK is necessary to find the early deviation of growth, mental and emotional development in children. The research was conducted at the IHC Kucaibecause studies have not been done before using SDIDTK sheet.Objective: To determine Preview Stimulation, Detection and Early InterventionDevelopmental (SDIDTK) In Toddlers (Age 1-5 Years) at IHC Kucai 2009.Methods: The study was a descriptive cross-sectional quantitative approach. The samplesused were Accidental sampling, sample research is Toddlers in IHC Kucai sample in thisstudy 84 Toddler. The research instrument used scales, metlin and SDIDTK sheet. Types ofdata are primary and secondary data. Analysis of the data used is the univariate analysis.Results: The result showed Stimulation, Detection and Early Intervention on Toddler GrowthIn IHC Kucai In 2009 most of the growth is normal infants were 44 respondents (83%),normal childhood development by 44 respondents (83%), children do not have a problememotional mental by 47 respondents (88.7%), respondents had a low risk of autism by 50respondents (94.3%), do not have attention deficit disorder and hyperactivity by 48respondents(90.6%).Conclusion: Most of the Stimulation, Detection and Early Intervention Toddler Growth isgood. Keywords: Stimulation, Detection and Early Intervention Developmental, Toddlers (age 1-5 years).